Red Blood Cell Alloimmunization after Blood Transfusion. - Schonewille, Henk (LUP Dissertaties., 2007)
An investigation of the safety implications of pre-transfusion policy which requires the patient's serum to be tested for the presence of irregular red blood cell antibodies.